Avaliação da resistência de união da resina composta ao esmalte desmineralizado submetido à remineralização e infiltração resinosa de lesão de cárie - Lacerda, Ana Júlia Farias [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim of this study was to evaluate, through microtensile test, the bond strength of composite resin restorations made of sound enamel, demineralized, remineralized with saliva, fluoride and infiltratado with resin material, associated with two types of adhesive systems: Total conditioning (Single Bond Universal - AS) and self-etching (Clearfil S3 Bond - AC) and the absence or presence of aging by thermal cycling. We used 240 bovine teeth with enamel surfaces planned, which were divided into 10 groups (n = 12) according to the type of substrate and adhesive system used: G1: (No Treatment) Enamel Healthy + AS; G2: (No treatment) Enamel Healthy + AC; G3: demineralized + AS; G4: demineralized + AC; G5: demineralized + remineralized with Saliva + AS; G6: demineralized + remineralized with Saliva + AC; G7: demineralized + remineralized Fluoride + AS; G8: demineralized + remineralized Fluoride + AC; G9: demineralized + infiltrate with resin (ICON) + AS; G10: demineralized + infiltrate with resin (ICON) + AC. Composite restorations Z-350 and half of the specimens were prepared were subjected to thermal cycling and non-cycling group was only stored for 24 h in distilled water at 37 ºC. For the microtensile test were carried out sections in the teeth to obtain samples adhesive area of about 1 mm2. SEM was performed for further analysis of the adhesive interface. We used the ANOVA three factors (Treatment of Adhesive System Enamel X X Thermal Cycling), followed by the Tukey test (α = 5%). Significant differences were observed for the three factors: treatment of enamel, Adhesive System and Thermal Cycling. The average values in MPa (± standard deviation) for the treatment of enamel factor: Control = 27.34 (± 7.45) a; Demineralized = 11.76 (± 6.69) b; Saliva = 13.78 (± 7.63) b; Fluoride = 15.10 (± 6.86) be ICON = 24.03 (± 7.63) a. For System factor Adhesive: AS = 21.75 (± 13.95) to ...

O objetivo desse estudo foi avaliar, por meio de teste de microtração, a resistência de união de restaurações de resina composta confeccionadas em esmalte hígido, desmineralizado, remineralizado com saliva, remineralizado com flúor e infiltratado com material resinoso, associado a dois tipos de sistemas adesivos: condicionamento total (Single Bond Universal - AS) e autocondicionante (Clearfil S3 Bond - AC) e a ausência ou presença do envelhecimento por ciclagem térmica. Foram utilizados 240 dentes bovinos com superfícies de esmalte planificadas, que foram divididos em 10 grupos (n = 12) de acordo com o tipo de substrato e sistema adesivo utilizado: G1 - (Sem Tratamento) Esmalte Íntegro + AS; G2 - (Sem tratamento) Esmalte Íntegro + AC; G3 - Desmineralizado + AS; G4 - Desmineralizado + AC; G5 - Desmineralizado + Remineralizado com Saliva + AS; G6 - Desmineralizado + Remineralizado com Saliva + AC; G7 - Desmineralizado + Remineralizado com Flúor + AS; G8 - Desmineralizado + Remineralizado com Flúor + AC; G9 - Desmineralizado + Infiltrado com resina (ICON) + AS; G10 - Desmineralizado + Infiltrado com resina (ICON) + AC. Foram confeccionadas restaurações de resina composta Z-350 e metade dos espécimes foram submetidos a ciclagem térmica e o grupo não ciclado foi apenas armazenado durante 24 h em água destilada à 37 ºC. Para o teste de microtração foram realizadas as secções nos dentes para obtenção de amostras com área adesiva de aproximadamente 1 mm2. Foi realizada MEV para análise complementar da interface adesiva. Utilizou-se o teste estatístico ANOVA três fatores (Tratamento do Esmalte x Sistema Adesivo x Ciclagem Térmica), seguido do Teste de Tukey (α = 5%). Foram observadas diferenças significantes para os três fatores: Tratamento do Esmalte, Sistema Adesivo e Ciclagem Térmica. Os valores de média em MPa (± Desvio-padrão) para o fator Tratamento do esmalte: Controle = 27,34...
Keywords: Esmalte dentário; Cárie dentária; Remineralização dentária; Dental caries